Inequality and Growth in Modern China 2008
DOI: 10.1093/acprof:oso/9780199535194.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Development Strategies and Regional Income Disparities in China*

Abstract: This paper argues that the regional income gap of China is endogenously determined by its long-term economic development strategy. Development strategies can be broadly divided into two mutually exclusive groups: (i) the comparative advantage-defying (CAD) strategy, which attempts to encourage firms to deviate from the economy's existing comparative advantages in their entry into an industry or choice of technology; and (ii) the comparative advantage-following (CAF) strategy, which attempts to facilitate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In recent years, regional differences have become increasingly noticeable. As for regional development trends in China, Lin & Liu (2008) carried out a study on the provincial economic gap of mainland China with the variation coefficient and Gini coefficient. They showed that the regional gap in mainland China has grown wider since the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, regional differences have become increasingly noticeable. As for regional development trends in China, Lin & Liu (2008) carried out a study on the provincial economic gap of mainland China with the variation coefficient and Gini coefficient. They showed that the regional gap in mainland China has grown wider since the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…To provide a contextual background of our empirical analysis, we first recognize that the WDS was designed to remedy the regional income inequalities documented in the extant literature (e.g., Jian et al, 1996;Wu, 2001;Grewal and Sun, 2002;Lin and Liu, 2005;Kanbur and Zhang, 2009;Fleisher et al, 2010;Huang and Todd, 2010;Li and Wei, 2010). Further, infrastructure investments gained national policy priority in the 1980s (Jin, 1994).…”
Section: Introductionmentioning
confidence: 99%